IMPACT OF COMMERCIAL GRADE HEXAGOR AND SUMIDON ON BEHAVIOUR AND SOME ASPECTS OF CARBOHYDRATE METABOLISM IN THE FISH CYPRINUS CARPIO - GHOSH, T. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1987)
The toxic impact of two organophosphates viz. Hexagor and Sumidon at their sublethal level on biochemical parameters of blood, liver, muscle and enzyme activities in gills, brain, muscle, liver, kidney and intestine of a fresh water teleost, Cyprinus carpio was studied after 15, 30, 45 and 60 days. The alternations produced by the pesticide are more pronounced after 15 days. Most of the behavioural parameters i e surfacing activity, distance travelled tremors, convulsions and opercular movement were enhanced under stress of Hexagor and Sumidon. The glycogen content of liver and muscle was inhibited whereas blood glucose level was elevated in all the exposed fish. Blood cholesterol and free fatty acid was found to be depleted in all the exposure periods. In gills, brain, muscle and liver, the LDH activity was elevated in the pesticide exposed fish. Decrease in PDH activity was observed in all the six tissues; SDH activity was inhibited in gills, muscle, brain & liver. The results are discussed in relation to the shift in the respiratory metabolism from aerobiosis to anaerobiosis and utilization of organic reserves yielding excess energy to compensate the possible toxic stress.